Wood chemical characterization of Acacia mangium and Calophyllum brasiliense grown in plantation (Research, Society and Development, 2024)
This study aimed to characterize and compare the physical and chemical properties of wood from 15-year-old Acacia mangium and 16-year-old Calophyllum brasiliense plantation trees. Specific data is provided on basic density, extractives, holocellulose, lignin, ash content and the highest heating value, as well as the linear correlations between them were performed. We observed similar mean values of basic density, despite statistical differences were found in lignin and holocellulose contents. The results for the higher heating value (19.5 kJ kg−1) were noteworthy, as they are positively associated with the extractive content (8.3%) and lignin content (26.0%) of A. mangium and C. brasiliense, respectively. Furthermore, the relationships found between the basic density of C. brasiliense wood, and its chemical properties were different from those expected, suggesting that other analyses should be carried out on the wood in order to fully understand it. Both species demonstrate calorific values suitable for biomass production, suggesting the potential use of their residues for pellet and briquette manufacturing. The findings have provided valuable information on the quality and behavior of wood, especially to contribute to the sustainable use of forest resources.